2016
DOI: 10.1136/bmjresp-2016-000152
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of immunoglobulins and severity of community-acquired pneumonia

Abstract: InstructionThere is evidence of a relationship between severity of infection and inflammatory response of the immune system. The objective is to assess serum levels of immunoglobulins and to establish its relationship with severity of community-acquired pneumonia (CAP) and clinical outcome.MethodsThis was an observational and cross-sectional study in which 3 groups of patients diagnosed with CAP were compared: patients treated in the outpatient setting (n=54), patients requiring in-patient care (hospital ward)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 31 publications
2
23
1
Order By: Relevance
“…Feldman et al could not find any differences in IgG subclass levels between 66 non-ICU and ICU patients with CAP [ 31 ]. By contrast, a recent Spanish study of 418 CAP patients showed a significant association between low Ig levels (IgG/IgG1) in patients with a CURB-65 severity score of 4 and 5, in ICU patients vs non-ICU patients (IgG/IgG1/IgG2), and with 30-day mortality (IgG/IgG1/IgG2) [ 13 ]. Low levels of IgG2 have been observed in patients with severe H1N1 influenza in China [ 32 ] and Australia [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Feldman et al could not find any differences in IgG subclass levels between 66 non-ICU and ICU patients with CAP [ 31 ]. By contrast, a recent Spanish study of 418 CAP patients showed a significant association between low Ig levels (IgG/IgG1) in patients with a CURB-65 severity score of 4 and 5, in ICU patients vs non-ICU patients (IgG/IgG1/IgG2), and with 30-day mortality (IgG/IgG1/IgG2) [ 13 ]. Low levels of IgG2 have been observed in patients with severe H1N1 influenza in China [ 32 ] and Australia [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] The few available studies measuring Igs in adult CAP have shown lower levels in patients as compared with controls and also in hospitalized vs ambulatory cases. [ 5 ] However, they disagree on the class/subclass of Igs compromised. [ 5 7 ] The use of antibodies level as a severity biomarker in these patients is also controversial, and while some studies found no relationship, [ 6 , 8 , 9 ] others have associated low IgG or IgA levels with severity and/or lethality.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] However, they disagree on the class/subclass of Igs compromised. [ 5 7 ] The use of antibodies level as a severity biomarker in these patients is also controversial, and while some studies found no relationship, [ 6 , 8 , 9 ] others have associated low IgG or IgA levels with severity and/or lethality. [ 5 , 10 , 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…IgM plays a critical role in the immediate defense against severe bacterial infection. Reduced IgM levels have been observed in patients with CAP, sepsis, and severe pandemic influenza; consequently, interest in add-on therapy with IgM-enriched preparations has increased [ 10 12 ]. The evidence for IgM-enriched Ig preparations in patients with severe sepsis and septic shock is incompletely understood, although systematic reviews have generally concluded that IgM-enriched Ig preparations are associated with a reduction in mortality [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%